Spin-Off Policy of Sharia Bank: Is It Profitable? - Aam Slamet Rusydiana; Abrista Devi; Fatin Hasib; Lina Rani (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2019)
According to Law no. 21 Year 2008, the Sharia Business Unit (SBU) owned by a Conventional Commercial Bank (CCB) is required to separate from its Parent Bank before year 2023. Some Sharia Business Units have initiated a separation step from Conventional Commercial Bank. On the other hand, they are required to keep the level of efficiency in running its business operations. This paper is intended to analyze the efficiency level of Sharia Business Units that have separated from its parent and then compare whether there is difference of efficiency level between before and after separation. The method used is Data Envelopment Analysis (DEA) and Paired Sample t-Test.The results show that based on the total average efficiency of all sharia banks spin off (in this case four sharia banks namely BNI Sharia, BRI Sharia, BJB Sharia and Bukopin Sharia Bank), there occur a decrease in efficiency technically and also pure the technical itself in sharia banks starting from before and after the spin off. This can be read because in the early periods of spin off there was a cost adjustment on the shariah bank spin off. Sharia banks require a 'weaning' from their parents. Nevertheless, there is no statistically significant difference in efficiency levels between before and after the spin off. This should be a booster for other Sharia Business Units to take the decision to spin off immediately, of course, accompanied by careful and prudent planning and implementation.